RNA Virus Discovery Sheds Light on the Virome of a Major Vineyard Pest, the European Grapevine Moth (Lobesia botrana) - Humberto Debat; Sebastian Gomez-Talquenca; Nicolas Bejerman (Viruses)
The European grapevine moth (Lobesia botrana) poses a significant threat to vineyards worldwide, causing extensive economic losses. While its ecological interactions and control strategies have been well studied, its associated viral diversity remains unexplored. Here, we employ high-throughput sequencing data mining to comprehensively characterize the L. botrana virome, revealing novel and diverse RNA viruses. We characterized four new viral members belonging to distinct families, with evolutionary cues of cypoviruses (Reoviridae), sobemo-like viruses (Solemoviridae), phasmaviruses (Phasmaviridae), and carmotetraviruses (Carmotetraviridae). Phylogenetic analysis of the cypoviruses places them within the genus in affinity with other moth viruses. The bi-segmented and highly divergent sobemo-like virus showed a distinctive evolutionary trajectory of its encoding proteins at the periphery of recently reported invertebrate Sobelivirales. Notably, the presence of a novel phasmavirus, typically associated with mosquitoes, expands the known host range and diversity of this family to moths. Furthermore, the identification of a carmotetravirus branching in the same cluster as the Providence virus, a lepidopteran virus which replicates in plants, raises questions regarding the biological significance of this moth virus to the grapevine host. We further explored viral sequences in several publicly available transcriptomic datasets of the moth, indicating potential prevalence across distinct conditions. These results underscore the existence of a complex virome within L. botrana and lay the foundation for future studies investigating the ecological roles, evolutionary dynamics, and potential biocontrol applications of these viruses in the L. botrana–vineyard ecosystem.